Respostas
respondido por:
1
Tc=m(C).a
Tb-Tc=m(B).a
P(A)-Ta=m(A).a ...somando as equacoes
-----------------------
P(A)=(m(A)+m(B)+m(C)).a
2.10=(2+4+4).a
a=20/10
a=2 m/s²
Tc=m(C).a
Tc=4.2
Tc=8 N
Tb-Tc=m(B).a
Tb-8=4.2
Tb=8+8
Tb=16 N
boa sorte :)
Tb-Tc=m(B).a
P(A)-Ta=m(A).a ...somando as equacoes
-----------------------
P(A)=(m(A)+m(B)+m(C)).a
2.10=(2+4+4).a
a=20/10
a=2 m/s²
Tc=m(C).a
Tc=4.2
Tc=8 N
Tb-Tc=m(B).a
Tb-8=4.2
Tb=8+8
Tb=16 N
boa sorte :)
blino996:
Aeeooooo vlw.
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás